Internet of Things (IoT) Technologies in Cybersecurity: Challenges and Opportunities - Grzegorz Kołaczek (Applied Sciences)
The continuous development and increasing availability of Internet of Things (IoT) solutions have led to an era of connectivity in which everyday objects—from household appliances to industrial machines—are connected via the Internet [...]